Komparasi Minat Belajar Siswa Kelas III MI Ma’arif Mayak Ponorogo dengan Menggunakan Alat Peraga Papan Pecahan - Kurnia Hidayati; Nur Qhoufi Khuzaini (Indonesian Mathematics Education Journal, 2024)
Interest is a person's favourite, favourite thing about something. The tedious learning process of mathematics tends to make students less interested in learning material, so one of the efforts made in the learning process is by using fraction board props on simple fraction material. The research method used is a comparison with the independent sample t-test. The research was conducted at MI Ma'arif Mayak Ponorogo with a sample size of 50 students consisting of 2 classes, namely class 3a as the experimental class and class 3b as the control class. The data collection technique used a questionnaire—technical data analysis using quantitative descriptive data and inferential statistics. The results of the study are 1) the learning interest of MI Ma'arif Mayak Ponorogo students who use fraction board props in the high category 8%, medium category 84% and low category 8%; 2) the learning interest of MI Ma'arif Mayak Ponorogo students who do not use fraction board props in simple fraction material in the high category 20%, medium category 64%, and low category 16% and 3) There is a significant difference between the learning interest of MI Ma'arif Mayak Ponorogo students who use and do not use the fraction board props with t-count 3.159 and t-table 2.201 at the 5% significance level.